الظواهر المدانة في مجال التربية والتعليم - رحيم نعيمه, سمر; جلال احمد, ريزان (Journal of College of Education, 2020)
The education is considered  one of the  main and  important  matters  for every country  since  it is deemed as a key for  its development  and its growth .This sector  suffers from  many essential problems , especially after 2003 , most notably reasons lying in the  non- security conditions  prevailing over the country . This led to  losing discipline and commitment  as well as respect  and this ,in return caused  deterioration in the education  in the country and problems  suffered by the  teaching  programs as well, most  notably is the  method of teaching adhered in this country  and this method is deemed to be an old one. It is worthy to be mentioning that many experts  and those interested   in the educational programs  warned  to necessarily address  this  phenomena immediately and to not stand idle beside this matter  in order not to be converted into an obstacle .Thus ,  in our current research we have  referred  to most important problems facing  the education after 2003  , depending in some problems  on daily and personal  notes,  trying to give some  genuine  solutions that could be applied  to confront  the problems.